2008
DOI: 10.1021/la801962j
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Membrane Itself Can Affect Gene Expression in the Escherichia coli Cell-Free Translation System

Abstract: A possible role of a model biomembrane, liposome, in gene expression was investigated by using the cell-free translation system. A reporter protein, green fluorescence protein (GFP), was expressed in vitro with and without liposome prepared with 1-palmitoyl-2-oleoyl- sn-glycero-3-phosphatidyl chorine (POPC) and cholesterol (Ch) (5.7 mM lipid concentration). In the presence of POPC/Ch liposome, the fluorescence intensity of produced GFP was found to be 1.67 times higher than that in the control after 18 h of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
“…A liposome membrane is effective in its use as a platform to perform the above purpose because it looks after the fundamental characteristics of a conventional extraction system and the recognition surface of the biomolecule ( Figure 1). In practice, there are many reports on the possible role of a liposome membrane to recognize various molecules , such as asymmetric recognition [56-57], metal affinity [4], peptide recognition [7,58], enzyme-like function [8,59], RNA recognition [6,42,48], and others [9,28] (Figure 8). membrane modules [61], and hydrogel immobilization of the liposomes at high concentration ( Figure 9) [62].…”
Section: Conclusion and Future Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the antioxidative activity 4 ~ 6) or gene expression system 3) have been well constructed on liposome membrane, which is called as LIPOzyme (liposome + enzyme). The previous reports on the LIPOzyme have indicated that the lipid composition and the phase state of lipid membrane, such as liquid-ordered (lo) phase, liquid-disordered (ld) phase and their mixture (ld + lo) phase, could control their function 5) .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the liposome itself can affect the protein expression of the GFP gene 10) .…”
Section: Introductionmentioning
confidence: 99%